Conservation and environmental management reimagined: Toward anti-oppressive futures - Laura German; Jesse Abrams; Cory L. Struthers; Sherry Pictou; C. Brock Woodson; Suneel Kumar; Tommy Cabe; Roger Merino; Elizabeth King (Proceedings of the National Academy of Sciences, 2026)
Conservation and environmental management are under increased scrutiny as the embeddedness of oppressive practices has gained wider societal and scholarly attention. As conservation and environmental practitioners and scholars grapple with foundational assumptions and practices of the field, there remains a pressing need to identify persistent problematic legacies and articulate a positive vision for conservation grounded in an ethic of justice. To help advance this conversation, we present a framework of four intersecting dimensions of oppression: 1) the physical or material manifestations of conservation and environmental management; 2) the knowledge practices and assumptions that inform and underpin conservation and environmental visions and decision-making; 3) the modes of governance associated with conservation and environmental practice; and 4) the forms of relational praxis implicitly and explicitly endorsed and/or imposed in conservation and other environmental arenas. We explain the framework through an analysis of the legacy of fortress conservation, then illustrate the framework’s wider application to diagnose ongoing elements of oppression in other environmental arenas (wildland fire, riverine flows). We then review prominent strategies and visions for moving forward for both nature and people to highlight both positive steps being taken and the utility of the framework in ensuring emergent environmental paradigms avoid the pitfalls of the past. Viewing each dimension of oppression as moveable levers to promote antioppressive conservation futures, we conclude with a set of questions to help conservation and environmental management scientists and practitioners identify where oppression might be manifest in their own work, and begin to embody antioppressive practices.